Identify. Quantify. Predict. Why Immunologists Should Widely Use Molecular Imaging for Coronavirus Disease 2019 - Juengling, Freimut D.; Maldonado, Antonio; Wuest, Frank; Schindler, Thomas H. (Frontiers in Immunology, 2021)
Molecular imaging using PET/CT or PET/MRI has evolved from an experimental imaging modality at its inception in 1972 to an integral component of diagnostic procedures in oncology, and, to lesser extent, in cardiology and neurology, by successfully offering in-vivo imaging and quantitation of key pathophysiological targets or molecular signatures, such as glucose metabolism in cancerous disease. Apart from metabolism probes, novel radiolabeled peptide and antibody PET tracers, including radiolabeled monoclonal antibodies (mAb) have entered the clinical arena, providing the in-vivo capability to collect target-specific quantitative in-vivo data on cellular and molecular pathomechanisms on a whole-body scale, and eventually, extract imaging biomarkers possibly serving as prognostic indicators. The success of molecular imaging in mapping disease severity on a whole-body scale, and directing targeted therapies in oncology possibly could translate to the management of Coronavirus Disease 2019 (COVID-19), by identifying, localizing and quantifying involvement of different immune mediated responses to the infection with SARS-COV2 during the course of acute infection and possible, chronic courses with long-term effects on specific organs. The authors summarize current knowledge for medical imaging in COVID-19 in general with a focus on molecular imaging technology, and provide a perspective for immunologists interested in molecular imaging research using validated and immediately available molecular probes, as well as possible future targets, highlighting key targets for tailored treatment approaches as brought up by key opinion leaders (1,2)